ANALISIS YURIDIS MENGENAI PERTANGGUNGJAWABAN PIDANA PENGGUNA JASA PROSTITUSI DALAM PERSPEKTIF KUHP - Yeremia Simangunsong, Mesites; Dharma Kusuma, A. A. Gede Agung (Kertha Wicara : Journal Ilmu Hukum, 2014)
The life dynamics of society felt so complex. When a phenomenan comes up in this global world and make the prostitution as a job nowadays. The prostitution service user is a component that brings big influence to a bad behavior for society. The issue that will deliver in this paper is, the liability of prostitution user in Criminal Code pesrpective. Therefore this paper aims to identify and analyze the Criminal Code regarding the regulation of vigilantism. This research use normative method that focused on literature reasearch. In terms of criminal responsibility is required to be clear and firm. Therefore, a judicial review regarding criminal responsibility necessary, that will lead to the renewal of the criminal law, specially on prostitution service users.
Keywords: Criminal Responsibility, Prostitution Service Users